Announcements - Bean, C.; Moore, J. (Review of Economic Studies, 1989)
Journal Article Announcements Get access Charles Bean, Charles Bean Search for other works by this author on: Oxford Academic Google Scholar John Moore John Moore Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 56, Issue 4, October 1989, Page 475, https://doi.org/10.1093/restud/56.4.475 Published: 01 October 1989